Practical GameMaker Projects Build Games with GameMaker Studio 2 - Tyers, Ben (Apress, 2018)
Make 10 simple, casual games, and learn a ton of GML coding along the way. Each of these games is the kind you can play when you have a minute or two free, and are great for playing on your PC, or exported to HTML5 or Android. Each game in Practical GameMaker Projects has its own chapter that explains the process of making each game, along with sketches, screenshots, coding, explanations, and tips. For each game there is a YYZ project file of the completed game that is ready to load and play. Also, all resources are available so you can make the game as you follow along in the book. Each chapter has an introduction that explains what the aim of the game is, followed by a design and coding section which will cover the coding of the game. You're free to re-use code in your own projects, both free and paid. At the end of each chapter there is a things-to-try page that gives you five things to add to the game to improve its playability or appearance - pushing you a little to improve your planning and GML skills. You will: Build 10 game applications using GameMaker Studio 2 Use the GameMaker Markup Language along the way Master the concepts behind each of the 10 game apps Design and code for each of the 10 game examples Try some add-ons for each of the 10 games.